Предмет:
МатематикаАвтор:
анонимУпростим выражение (x + 2)^2 + (2 * x - 1)^2.
Раскроем скобки и приведем подобные значения.
(x + 2)^2 + (2 * x - 1)^2 = x^2 + 2 * x * 2 + 2^2 + (2 * x)^2 - 2 * 2 * x * 1 + 1^2 = x^2 + 4 * x + 4 + 4 * x^2 - 4 * x + 1 = (x^2 + 4 * x^2) + (4 * x - 4 * x) + (4 + 1) = x^2 * (1 + 4) + x * (4 - 4) + 5 = x^2 * 5 + 0 + 5 = 5 * x^2 + 5 = 5 * (x^2 + 1);
В итоге получили, (x + 2)^2 + (2 * x - 1)^2 = 5 * (x^2 + 1).
Автор:
nicoleyxlcДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть